Biblioteka Uniwersytecka w Poznaniu jako „trzecie miejsce” - Chachlikowska, Aldona (Biblioteka Uniwersytecka w Poznaniu, 2016)
W artykule omawiam kulturotwórczą, wydawniczą i promocyjną działalność Biblioteki Uniwersyteckiej w Poznaniu, głównie na przestrzeni ostatnich 20 lat. Przedstawiam najważniejsze przejawy działalności kulturotwórczej, takie jak: Tydzień Bibliotek, Festiwal Nauki i Sztuki, Noc Naukowców, wystawy, Żywa Biblioteka, Poznańska Dyskusyjna Akademia Komiksu, Dyskusyjny Klub Książki. Prezentuję działalność wydawniczą: rocznik „Biblioteka”, serie: Prace Biblioteki Uniwersyteckiej w Poznaniu, Antiquitates Minutae, Libri Librorum i inne wydawane poza seriami pozycje. Tekst kończę opisem zadań w zakresie promowania instytucji. Aktywność, realizowana praktycznie od zarania dziejów Biblioteki, przeszła w ostatnich latach rewolucyjną zmianę. Stanowi to bez wątpienia odpowiedź na oczekiwania społeczne zarówno mieszkańców regionu, pracowników i studentów uczelni, jak i stałych użytkowników placówki, a jednocześnie jest elementem świadomej strategii. Jest to także podkreślanie roli największej placówki bibliotecznej w północno-zachodniej Polsce.

The present article discusses the culture making, editorial and promotional activity of the University Library in Poznań focusing mainly on the last twenty years. The most important manifestation of the library’s culture making activity are presented and include: Library Week, Festival of Science and Arts, Researchers’ Night, exhibitions, Living Library, Poznań Comics Discussion Academy, Book Discussion Club and many others. The presented editorial and publishing activities include: the annual library’s publication „Biblioteka”, the series: Prace Biblioteki Uniwersyteckiej w Poznaniu, Antiquitates Minutae, Libri Librorum and other publications published outside of the regular series. The article is concluded with an outline of the essential tasks to be fulfilled in order to promote the institution. The indicated activities, carried out virtually since the inception of the library, have recently gone through particularly dramatic and significant changes. Undoubtedly, however, they still constitute the core answer to the social expectations of the local population, library staff and students of the University alike, as well as the library’s permanent users. At the same time, this is a component element of a deliberate strategy undertaken by the institution. In addition, this contributes to underpinning the long-term viability of this largest library in North-West Poland.
Poznań University Library as the „third place"
Keywords: Biblioteka Uniwersytecka w Poznaniu; Poznań University Library; działalność kulturotwórcza; culture making activity; aktywność wydawnicza; publishing activity; promocja; promotion; Biblioteka 2.0; Library 2.0.